Tanggung Jawab Pelaku Usaha Atas Ketersedian Informasi Yang Tidak Lengkap dan Benar Melalui Media Elektronik - Rafiqi; Cahaya (Pelita Masyarakat, 2025)
This research aims to examine the responsibility of business actors in providing correct, complete, and non-misleading information through electronic media and its implications for consumer protection. The research method used is a normative juridical approach that examines various legal regulations related to the responsibility of business actors and their legal impact. Data collection is carried out through literature studies by reviewing legal documents, journals, reference books, and field research that includes observations and interviews with related parties in the Lower Medan City Government. Research results show that business actors have legal and ethical obligations to provide transparent information to consumers, while failure to fulfill these obligations can result in serious legal consequences, both civil, administrative, and criminal. Therefore, efforts are needed to increase information verification, public education, and strict regulatory enforcement to create a fair and trusted digital business environment